Efek Harga dan Perilaku Pemakaian Kontrasepsi - Darmawan, Dody Harris (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2018)
Abstract The behavior of spouses of fertile age (EFA) in choosing a contraceptive that will she wear is influenced by many factors. Previous research extensively covered socio-demographic factors correlated to the choice of contraception. Rationally, households in choosing a contraceptive based on the benefits of optimal and minimal costs. This study will discuss the price as reflecting rationality EFA determinant in choosing a contraceptive. By using data from the BKKBN Family Data Collection In 2015, this study will use the order logit models to determine causality or correlation between price and other determinants of the choice of contraception. It was found that the price of a statistically significant effect on the choice of contraception. Probability of contraceptive choices tend towards the long-term contraception with increases in the price of each contraception.